Marinha do Brasil e Programa Netuno: excelência gerencial como meio e uma Força Armada de qualidade como fim - Conceição, Marcelo Diógenes Rocha (2012)
This research approaches the transfer of the Total Quality Management Program GesPública to the Brazilian Navy military environment. GesPública focuses on the Brazilian Public Administration and Netuno Program was the name adopted in the Navy to operate the GesPública’s fundaments. Netuno Program was planned to be put into practical effect in all Brazilian Navy’s working areas. In fact, its fundaments are the same of GesPública. These fundaments intend to be useful in a comprehensive area of action, since bureaucratic procedures until military operations, whose principles are necessarily based on military doctrine. So, the Netuno Program concepts, whose are based on civil settings that call for more horizontal structures in organizations, faces the military environment, in which hierarchy and discipline are strong military principles. Henceforth, the goal of the study is to demonstrate the contributions Netuno Program can offer to Brazilian Navy. Literature and documents about the Navy, military doctrine, Total Quality Management Programs and other related issues are the main source. A content analysis methodology will be used to find categories associated to Brazilian Navy and Netuno Program. These categories will be compared in order to achieve the research targets.